2022
DOI: 10.3389/fgene.2022.989565
|View full text |Cite
|
Sign up to set email alerts
|

A genomic and transcriptomic study toward breast cancer

Abstract: Background: Breast carcinoma is well recognized to be having the highest global occurrence rate among all cancers, being the leading cause of cancer mortality in females. The aim of this study was to elucidate breast cancer at the genomic and transcriptomic levels in different subtypes so that we can develop more personalized treatments and precision medicine to obtain better outcomes.Method: In this study, an expression profiling dataset downloaded from the Gene Expression Omnibus database, GSE45827, was re-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[53][54][55] Several studies have demonstrated that KIF23 plays a critical role in tumorigenesis and cancer progression through the disruption of normal cytokinesis and centrosome formation, resulting in cell division arrest or abnormalities that contribute to the formation of aneuploid cells that promote tumorigenesis. High levels of KIF23 in tumor-affected tissues ere associated with a poor prognosis and are correlated with TNM stage [56][57][58] and recurrence in numerous tumors, Table 2. Function of the ten dentified hub genes.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Several studies have demonstrated that KIF23 plays a critical role in tumorigenesis and cancer progression through the disruption of normal cytokinesis and centrosome formation, resulting in cell division arrest or abnormalities that contribute to the formation of aneuploid cells that promote tumorigenesis. High levels of KIF23 in tumor-affected tissues ere associated with a poor prognosis and are correlated with TNM stage [56][57][58] and recurrence in numerous tumors, Table 2. Function of the ten dentified hub genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when gene expression in luminal A and luminal B tumors were compared with the designated PAM50 gene set, differences were observed in genes involved in the cell cycle and cell proliferation such as BIRC5, CCNB1, CDC20, CEP55, KIF2C, MELK, MKI67 and UBE2C (Tishchenko et al, 2016). Pathway enrichment shows that luminal A tumors amplify pathways associated with extracellular matrix organization and collagen formation, comtrasting to luminal B tumors that show enrichment of DNA repair pathways, similar to that of HER2-enriched tumors (Wang et al, 2022). Phenotypically, luminal A tumors expressing ER and PR have the lowest proliferation potential (Ki-67), and present with the best prognosis (Goldhirsch et al, 2013).…”
Section: Luminal Subtypesmentioning
confidence: 99%
“…Several studies have been conducted and published in the last few years using public databases such as GREIN and Gene Expression Omnibus (GEO) to predict potential biomarkers. Liu et al conducted a study of 1203 BC samples from The Cancer Genome Atlas Database and identified 1317 differentially expressed genes, with 744 genes showing upregulation and 573 genes showing downregulation 9 . Besides, Wang et al also used one data set (GSE45827) from the GEO database and identified distinct expression genes in BC 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al conducted a study of 1203 BC samples from The Cancer Genome Atlas Database and identified 1317 differentially expressed genes, with 744 genes showing upregulation and 573 genes showing downregulation. 9 Besides, Wang et al also used one data set (GSE45827) from the GEO database and identified distinct expression genes in BC. 10 Based on the examination of single transcriptome datasets, multiple studies have predicted different sets of hub genes for BC, 11 , 12 , 13 but none of them shared a single hub gene.…”
Section: Introductionmentioning
confidence: 99%